2017
DOI: 10.3347/kjp.2017.55.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of Dermacentor everestianus Hirst, 1926 (Acari: Ixodidae) under Laboratory Conditions

Abstract: This study investigated the development characteristics of Dermacentor everestianus under laboratory conditions. The time taken for D. everestianus to complete the whole life cycle was 110.2 days on average, and the average developmental durations of larvae and nymphs were 17.1 days and 29.5 days, respectively. The summation of the prefeeding, feeding, and preoviposition periods of females was 17.8 days, and the oviposition and egg incubation lasted for 18.1 days and 27.7 days, respectively. A highly positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The above studies showed that the average period of one tick life-cycle of females under laboratory conditions was ranged from 110.2 to 179 days, while 121 to 177.8 days under eld conditions [52][53][54][55][56][57][58][59]. However, the average periods showed seasonal differences [52][53][54][55][56][57][58][59]. D. nuttalli was widely distributed in northern China, including the sampling sites in Qinghai Province in this study [5,6,8].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The above studies showed that the average period of one tick life-cycle of females under laboratory conditions was ranged from 110.2 to 179 days, while 121 to 177.8 days under eld conditions [52][53][54][55][56][57][58][59]. However, the average periods showed seasonal differences [52][53][54][55][56][57][58][59]. D. nuttalli was widely distributed in northern China, including the sampling sites in Qinghai Province in this study [5,6,8].…”
Section: Discussionmentioning
confidence: 96%
“…concinna under eld conditions were characterized in China [52][53][54][55][56][57][58][59]. The above studies showed that the average period of one tick life-cycle of females under laboratory conditions was ranged from 110.2 to 179 days, while 121 to 177.8 days under eld conditions [52][53][54][55][56][57][58][59]. However, the average periods showed seasonal differences [52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation